COMBINATION OF STRENGTH AND ENDURANCE IN THE TRAINING OF HIGHLY QUALIFIED BOXERS - Nuriddin Abdullayev (Bright Mind Publishing, 2025)
This article explores the integration of strength and endurance in the training programs of highly skilled boxers, with a specific focus on optimizing physical performance in the context of modern boxing demands. Strength and endurance are two fundamental physical qualities that must coexist in a balanced manner to achieve peak performance in the ring. The study examines how training methodologies in Uzbekistan are adapting to modern requirements by incorporating complex workout plans, recovery strategies, and sport-specific conditioning. Emphasis is placed on the physiological interaction between anaerobic strength development and aerobic endurance capacity, particularly in highly skilled athletes. Findings suggest that a periodized and individualized training approach, grounded in scientific principles and tailored to a boxer’s personal needs, can enhance both explosive power and sustained physical effort. The article contributes practical recommendations for coaches and athletes and supports a more integrative approach to boxing training.
Keywords: Strength training, endurance, boxing performance, elite athletes, periodization, training methods, physical preparation, sport-specific fitness, recovery.